Analysis of Tofu Quality Control Using the Failure Mode and Effect Analysis (FMEA) Method at Tahu Gunung SME - Andreanta Sembiring; Reakha Zulvatricia (Universitas Muhammadiyah Palu, 2025)
Business competition that is increasingly dynamic, complex, and uncertain emphasizes company managers to think creatively and innovatively. Product quality plays an important role in maintaining customer trust and loyalty, so companies must focus on developing and controlling product quality to increase competitiveness and achieve competitive advantage. This study aims to analyze the factors that cause product failure and examine strategies in improving quality at SMEs Tahu Gunung. The research method uses the Failure Mode and Effect Analysis (FMEA) method by identifying and reducing potential failures to improve product quality through RPN values. The results of the analysis show the calculation of the highest RPN value of 210 is in the soybean soaking process with the risk of failure due to soaking carried out less or more than the specified time and the water in the soaking tub is not replaced with new water, then obtained the second highest RPN value of 192 in the tofu delivery process. From the results of the RPN calculation, improvements are focused on the soaking and tofu delivery stages, by emphasizing to employees to drain the water reservoir regularly and install a cover for the water tank. In the tofu delivery process, improvements that can be made are checking the tofu before the tofu is sent, using a cover box for the tofu container, and routinely cleaning the mold and box after use.